2022
DOI: 10.1097/md.0000000000031428
|View full text |Cite
|
Sign up to set email alerts
|

Clinical symptoms, endoscopic findings, and lower esophageal sphincter characteristics in patients with absent contractility

Abstract: Absent contractility is a rare esophageal motility disorder defined by high-resolution manometry which remains poorly understood in pathogenesis and management. We investigated the clinical symptoms, upper gastrointestinal endoscopy findings, and lower esophageal sphincter (LES) characteristics in adult patients diagnosed with absent contractility on high resolution manometry and factors associated with erosive esophagitis that were found on endoscopy in these patients. A cross-sectional study was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The abnormalities were recorded using esophageal manometry, in which the patients frequently suffered from both abnormal esophageal sphincter pressure and contraction (DLESP and DDEPC), as has been reported in other studies. 35 , 36 In addition, reflux was reported in most patients using pH monitoring, and Arif et al (2015) also reported a high prevalence of reflux in his study. 37 Consistent with the other study employing videofluorography, signs of esophageal reflux were reported in most patients.…”
Section: Discussionmentioning
confidence: 87%
“…The abnormalities were recorded using esophageal manometry, in which the patients frequently suffered from both abnormal esophageal sphincter pressure and contraction (DLESP and DDEPC), as has been reported in other studies. 35 , 36 In addition, reflux was reported in most patients using pH monitoring, and Arif et al (2015) also reported a high prevalence of reflux in his study. 37 Consistent with the other study employing videofluorography, signs of esophageal reflux were reported in most patients.…”
Section: Discussionmentioning
confidence: 87%
“…Subsequent studies from Spain (43.1%) [ 25 ], Japan (40.7%) [ 26 ], the United States (37.3%) [ 27 ], and Israel (21.6%) [ 28 ] confirmed that a significant percentage of AC patients have an underlying rheumatologic or autoimmune disease. In contrast, in a study from Vietnam, none of the 204 patients with AC had any rheumatologic disease [ 29 ]. These findings are summarized in Table 2 .…”
Section: Ac and Rheumatologic Diseasesmentioning
confidence: 99%
“…Additionally, the populations being evaluated are likely to have played a major role. From these studies, it appears that the study by Dao et al is an outlier, given its lack of any rheumatologic diseases [ 29 ], but so is the study by Laique et al , with its extremely high rate [ 4 ]. Thus, it appears that the true percentage of AC patients with an underlying rheumatologic disease is likely to be in the 21-43% range seen in most of the other studies, and not >80% as was found in the Laique et al study.…”
Section: Ac and Rheumatologic Diseasesmentioning
confidence: 99%